Long-term efficacy of risedronate: a 5-year placebo-controlled clinical experience. - Sorensen, O; Crawford, G; Mulder, H; Hosking, D; Gennari, C; Mellstrom, D; Pack, S; Wenderoth, D; Cooper, C; Reginster, J (2003)
Limited placebo-controlled data are available to assess the long-term fracture efficacy of bisphosphonates. In order to determine the effects of 5 years of risedronate treatment, we extended a 3-year, placebo-controlled vertebral fracture study in osteoporotic women for an additional 2 years; women who entered the extension study continued to receive 5 mg risedronate or placebo according to the original randomization, with maintenance of blinding. End points included vertebral and nonvertebral fracture assessments, bone mineral density measurements, and changes in biochemical markers of bone turnover. A total of 265 women (placebo, 130; 5 mg risedronate, 135) entered the study extension and 220 (83%) completed the additional 2 years. Fracture results observed in the study extension were consistent with those observed in the first 3 years. The risk of new vertebral fractures was significantly reduced with risedronate treatment in years 4 and 5 by 59% (95% confidence interval, 19 to 79%, P = 0.01) compared with a 49% reduction in the first 3 years. Rapid and significant decreases in markers of bone turnover observed in the first 3 years were similarly maintained in the next 2 years of treatment. Increases in spine and hip bone mineral density that occurred in the risedronate group during the first 3 years were maintained or increased with a further 2 years of treatment. The mean increase from baseline in lumbar spine BMD over 5 years was 9.3% (P < 0.001). This study demonstrates that the effects of risedronate over 3 years on vertebral fracture and BMD are maintained with a further 2 years of treatment.